Give Me ‘Naked’ Braces. - Ackerman, A. Frank; Lowney, Geoffrey A. (Communications of the ACM, 2015)
A reply by the author is presented in response to a letter to the editor on A. Frank Ackerman's published letter "Ban 'Naked' Braces," from the October 2015 issue.